TELAAH PEMIKIRAN ISLAM LIBERAL DALAM NOVEL “KEMI” KARYA ADIAN HUSAINI PERSPEKTIF PENDIDIKAN ISLAM - Siaturrahmah, Anni; Maimun (Rabbani: Jurnal Pendidikan Agama Islam, 2024)
This study aims to determine the model of liberal Islamic thought in the novel 'Kemi' by Adian Husaini and to analyze of the model of liberal Islamic thought in the novel "Kemi" by Adian Husaini from the perspective of Islamic education. This research uses a qualitative approach with a type of literature study. The results of the study show that there are 9 models of liberal Islamic thought, and these models have begun to spread in the world of education. Therefore, a new concept is needed in the world of education, as offered by Adian Husaini, namely the concept of ta'dib.